Musika sa makabayan teaching music in Makabayan 3 using the thematic and analogous approaches - Guadalupe, Jocelyn Timbol (2008)
The study aimed to compare the effects of the thematic approach and the analogous approach in integrating Music with Social Studies with respect to the achievement of Grade 3 public school students in the cognitive, psychomotor-listening and domains within the Revised Basic Education Curriculum framework...